Antidepressant discontinuation before or during pregnancy and risk of psychiatric emergency in Denmark: A population-based propensity score-matched cohort study. - Xiaoqin Liu; Nina Molenaar; Esben Agerbo; Natalie C Momen; Anna-Sophie Rommel; Angela Lupattelli; Veerle Bergink; Trine Munk-Olsen (PLoS Medicine, 2022)
Background Women prescribed antidepressants face the dilemma of whether or not to continue their treatment during pregnancy. Currently, limited evidence is available on the efficacy of continuing versus discontinuing antidepressant treatment during pregnancy to aid their decision. We aimed to estimate whether antidepressant discontinuation before or during pregnancy was associated with an increased risk of psychiatric emergency (ascertained by psychiatric admission or emergency room visit), a proxy measure of severe exacerbation of symptoms/mental health crisis. Methods and findings We carried out a propensity score-matched cohort study of women who gave birth to live-born singletons between January 1, 1997 and June 30, 2016 in Denmark and who redeemed an antidepressant prescription in the 90 days before the pregnancy, identified by Anatomical Therapeutic Chemical (ATC) code N06A. We constructed 2 matched cohorts, matching each woman who discontinued antidepressants before pregnancy (N = 2,669) or during pregnancy (N = 5,467) to one who continued antidepressants based on propensity scores. Maternal characteristics and variables related to disease severity were used to generate the propensity scores in logistic regression models. We estimated hazard ratios (HRs) of psychiatric emergency in the perinatal period (pregnancy and 6 months postpartum) using stratified Cox regression. Psychiatric emergencies were observed in 76 women who discontinued antidepressants before pregnancy and 91 women who continued. There was no evidence of higher risk of psychiatric emergency among women who discontinued antidepressants before pregnancy (cumulative incidence: 2.9%, 95% confidence interval [CI]: 2.3% to 3.6% for discontinuation versus 3.4%, 95% CI: 2.8% to 4.2% for continuation; HR = 0.84, 95% CI: 0.61 to 1.16, p = 0.298). Overall, 202 women who discontinued antidepressants during pregnancy and 156 who continued had psychiatric emergencies (cumulative incidence: 5.0%, 95% CI: 4.2% to 5.9% versus 3.7%, 95% CI: 3.1% to 4.5%). Antidepressant discontinuation during pregnancy was associated with increased risk of psychiatric emergency (HR = 1.25, 95% CI: 1.00 to 1.55, p = 0.048). Study limitations include lack of information on indications for antidepressant treatment and reasons for discontinuing antidepressants. Conclusions In this study, we found that discontinuing antidepressant medication during pregnancy (but not before) is associated with an apparent increased risk of psychiatric emergency compared to continuing treatment throughout pregnancy.